La création des « bibliothèques publiques » : trois instructions pour fonder un champ d’intervention de l’État et réorganiser une profession (1789 – an II) - Cécile Robin (In Situ)
The nationalisation of ecclesiastical libraries offered an opportunity to initiate public action on a national scale. The redistribution of books required preliminary measures of protection and inventory of these ‘literary riches’. The instructions written by Parisian authorities between 1789 and 1794 illustrate the emergence of a written heritage by the construction of a field for central state intervention, of a system of objects and of a repertoire of specialised capacities.